In/Visible Art - Tkacheva, Marina (project baikal, 2015)
The article analyses different forms of easel painting, monumental and decorative art and photography existing in modern universities. It observes how the function of art changes in the context of modernization of culture and higher education. The role of initiators of art spaces in universities is also featured.